2019
DOI: 10.1186/s12912-019-0389-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the experiences of being an ethnic minority student within undergraduate nurse education: a qualitative study

Abstract: BackgroundStudents studying in a country where another language is spoken face multiple challenges including their ability to fully integrate with peers and academic pressures in trying to obtain an undergraduate nursing degree. The aim of the study was to explore the lived experiences of students, from varying cultural and ethnic backgrounds, undertaking an undergraduate nursing degree.MethodsThe study adopted a qualitative design and eight individual semi-structured interviews were conducted. The interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…The students conveyed that the feeling of missing personal relations with other students became a stressor for them. Social and academic isolation can have major consequences when acquiring professional knowledge [10,34,35]. Such ndings were also reported in another study based on a national sample where the nursing students showed strong feelings of social and academic isolation during the pandemic [36].…”
Section: Discussionsupporting
confidence: 57%
“…The students conveyed that the feeling of missing personal relations with other students became a stressor for them. Social and academic isolation can have major consequences when acquiring professional knowledge [10,34,35]. Such ndings were also reported in another study based on a national sample where the nursing students showed strong feelings of social and academic isolation during the pandemic [36].…”
Section: Discussionsupporting
confidence: 57%
“…The students conveyed that the feeling of missing personal relations with other students became a stressor for them. Social and academic isolation can have major consequences when acquiring professional knowledge [10,34,35]. Such ndings were also reported in another study based on a national sample where the nursing students showed strong feelings of social and academic isolation during the pandemic [36].…”
Section: Discussionmentioning
confidence: 52%
“…This might be explained by the lesser integration of this dimension within PT and baccalaureate students. This may be the case due to the fact that the student groups at these educational stages count on students from a highly specific contextual area who do not have the chance to work with other cultures, moving away from the normalization of multiculturality (Bhatnagar, 2017; Flateland et al, 2019). Thus, it can be established that, for this context and educational stage, cultural sensitivity in the workplace is observed as something extrinsic to this setting, being considered as something potentially more relevant in other contexts or higher educational stages (Aktoprak et al, 2018; Manning et al, 2017).…”
Section: Discussion and Applications To Practicementioning
confidence: 99%